A method for preparing a platinum-carbon catalyst, a platinum-carbon catalyst, and a catalyst coating film
By using the coordination reaction of the platinum precursor with the polyol and dispersion additive in the preparation of platinum carbon catalyst, combined with the addition of a carbon support, the problems of high agglomeration and poor distribution uniformity of platinum nanoparticles were successfully solved, and the high electrochemical active area and good stability of the platinum carbon catalyst were achieved, while simplifying the process and improving production efficiency.
Patent Information
- Application Number
- CN202211339554.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-10-26
AI Technical Summary
In the prior art, when preparing platinum carbon catalysts, platinum nanoparticles have high agglomeration and poor distribution uniformity, resulting in low electrochemical active area and poor stability, and complex processes and low production efficiency.
A platinum precursor is mixed with a polyol solvent, a dispersion additive solution is added for coordination reaction, and a carbon support polyol slurry is added, and a platinum carbon carbon catalyst is prepared after heating, reducing, concentration and drying. This method ensures that the platinum nanoparticles are evenly dispersed on the carbon support by controlling the order of raw materials and the addition of dispersion additives.
The prepared platinum carbon catalyst has weak agglomeration, high electrochemical active area, good stability, excellent performance, simple operation, no harmful impurities, avoiding complex washing and purification processes, and significantly improving production efficiency.
Smart Images

Figure CN115458755B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of platinum-carbon catalysts, and in particular to a preparation method of a platinum-carbon catalyst, a platinum-carbon catalyst and a catalyst coating film. Background Art
[0002] Platinum-carbon catalysts are widely used in fuel cells, electrolyzers, petrochemicals, chemical pharmaceuticals, and automobile exhaust purification. Platinum reserves are limited and expensive. In order to improve the utilization efficiency of platinum, the amount of platinum used can be greatly reduced by evenly loading platinum nanoparticles on carbon carrier materials, thereby reducing material costs.
[0003] However, the platinum-carbon catalysts prepared by conventional methods still have the problems of relatively large platinum particle size, high agglomeration of platinum nanoparticles, and poor distribution uniformity. The utilization rate of platinum atoms is low, resulting in low electrochemical active area and poor stability of platinum-carbon catalysts.
[0004] For example, in the common process of preparing ultrafine platinum-based nanocrystals, protective agents such as oleylamine and polyvinyl pyrrolidone are mainly added. These protective agents can be used as surface ligands, have appropriate complexation with metal ions, and can protect nanoparticles from agglomeration during the synthesis process. However, these agents have strong adsorption on the surface of platinum-based nanoparticles, and the cleaning of nanoparticles is relatively complicated and troublesome, and it is difficult to obtain a clean surface, which limits the exposure of catalytic sites and reduces catalytic activity. For example, Chinese invention patent CN102903537 B discloses a method for preparing multi-walled carbon nanotube-loaded high-density and high-dispersion nano-platinum electrodes. In a polyol reaction system, polyvinyl pyrrolidone is used as an inhibitor to achieve controllable preparation of platinum nanoparticles, but polyvinyl pyrrolidone has a strong coating on the surface of platinum nanoparticles, and usually needs to be removed by high-temperature heat treatment. The subsequent high-temperature treatment not only increases the preparation process, but also easily leads to sintering of platinum particles during high-temperature heat treatment. Therefore, this solution of suppressing the agglomeration of metal particles by adding protective agents often requires additional steps in the subsequent process to remove the side effects caused by the protective agent. In fact, the polyol method does not require the addition of surfactants. There are two or more hydroxyl groups in the molecular structure of polyols, which have appropriate reducing and coordination properties. Polyols have high boiling points and high viscosity, which can ensure good crystallization during the material preparation process, facilitate the diffusion mechanism to control particle growth, and the reducing medium protects the metal state to avoid oxidation. However, in the polyol reaction system, it is often necessary to finely control the pH value and optimize the synthesis parameters to achieve the separation of the nucleation and growth steps of platinum nanoparticles in time, and to control the particle size of platinum colloids in the platinum reduction stage. However, the introduced alkaline metal cations will affect the stability of the redispersion of platinum nanoparticles in alcohol and water systems, resulting in agglomeration during the loading process and causing the uniformity of platinum dispersion on the carrier to deteriorate, and the introduced impurities require additional washing and purification processes. For example, Chinese invention patent CN112823880 A discloses a method that does not require the addition of surfactants, using small molecule polyols as reaction solvents and reducing agents to control the platinum particle size. However, the method uses inorganic alkali (NaOH, KOH) to regulate the pH of the reaction solution, and platinum reduction reaction is carried out in an alkaline system. In addition, the invention uses platinum precursors containing halogen elements (including chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate), and the introduction of chloride ions and alkaline metal cation impurities will affect the performance of the platinum-carbon catalyst. If chloride ions remain in the catalyst, chloride ions will be strongly adsorbed on the platinum surface, occupying the active sites on the platinum surface, and will block the adsorption of oxygen and the reduction reaction of oxygen in the electrochemical reaction, causing platinum poisoning and inactivation. In order to better remove impurities, a complex washing and purification process is usually added, for example: a large amount of deionized water is consumed to wash the catalyst multiple times, and ultrasound, stirring or pressure are applied during the washing process to accelerate ion movement and improve the washing and impurity removal effect, but this undoubtedly increases the preparation process and washing costs, and also makes the semi-continuous operation process of the platinum-carbon product production system complicated, greatly reducing production efficiency. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a platinum-carbon catalyst, a platinum-carbon catalyst and a catalyst coating film in view of the problems that platinum nanoparticles in the platinum-carbon catalyst prepared by the prior art have high agglomeration, poor distribution uniformity, poor performance, complicated process and low production efficiency. The platinum-carbon catalyst prepared by the method has platinum nanoparticles uniformly dispersed on a carbon carrier and weak agglomeration, and the platinum-carbon catalyst has a high electrochemical active area, good stability and excellent performance. At the same time, the method is simple to operate, does not introduce harmful impurities, does not need to add a complex washing and purification process on the production line, greatly improves production efficiency and is easy to promote.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a platinum-carbon catalyst comprises the following steps:
[0008] Step 1, mixing the platinum precursor and the polyol solvent evenly, then adding the dispersing aid solution, mixing evenly, and performing a coordination reaction at a temperature of 30° C. to 90° C. to obtain a first material;
[0009] Step 2, adding the carbon support polyol slurry to the first material obtained in step 1, mixing, and obtaining a second material;
[0010] Step 3, heating the second material obtained in step 2 to 125°C to 160°C and keeping it warm for 1h to 5h; cooling it to below 90°C; then adding deionized water and continuing to stir at a constant temperature of 50°C to 90°C for 1h to 5h to obtain the third material;
[0011] Step 4: After concentrating the third material obtained in step 3, dry and grind it to obtain a platinum-carbon catalyst.
[0012] The present invention provides a method for preparing a platinum-carbon catalyst, comprising the following steps: step 1, uniformly mixing a platinum precursor and a polyol solvent, then adding a dispersing aid solution, mixing, and performing a coordination reaction at a temperature of 30°C to 90°C to obtain a first material; step 2, adding a carbon carrier polyol slurry to the first material obtained in step 1, mixing, and obtaining a second material; step 3, heating the second material obtained in step 2 to 125°C to 160°C, and keeping the temperature for 1h to 5h; cooling to below 90°C; then adding deionized water, and continuing to stir at a constant temperature of 50°C to 90°C for 1h to 5h to obtain a third material; step 4, concentrating the third material obtained in step 3, and then performing a drying and grinding process to obtain a platinum-carbon catalyst. The method mainly uses carbon carrier, platinum precursor, polyol and dispersing agent as raw materials. By controlling the addition order and amount of the raw materials and the addition method of the dispersing agent and other factors, a platinum-carbon catalyst is prepared through the processes of mixing, reduction, concentration, drying and grinding. The dispersing agent can not only coordinate with platinum appropriately, but also serve as a pH regulator for the reaction system. The platinum-carbon catalyst prepared by this method has platinum nanoparticles uniformly dispersed on the carbon carrier with weak agglomeration, and the platinum-carbon catalyst has a high electrochemical active area, good stability and excellent performance. At the same time, the method is simple to operate, will not introduce harmful impurities, and does not need to add complex washing and purification processes to the production line, which greatly improves production efficiency and is easy to promote.
[0013] Further, in step 1, the platinum precursor is at least one of platinum nitrate, platinum acetylacetonate, hexahydroxyplatinic acid and diaminodinitroplatinum; the polyol solvent is at least one of ethylene glycol, propylene glycol, glycerol, butanediol, diethylene glycol, triethylene glycol and tetraethylene glycol; in step 2, in the carbon carrier polyol slurry, the carbon carrier is at least one of carbon black, activated carbon, graphite carbon, carbon nanotubes, graphene and mesoporous carbon; in the carbon carrier polyol slurry, the polyol is at least one of ethylene glycol, propylene glycol, glycerol, butanediol, diethylene glycol, triethylene glycol and tetraethylene glycol. Preferably, in step 1, the platinum precursor is at least one of platinum nitrate, platinum acetylacetonate and hexahydroxyplatinic acid; the type of polyol in the carbon carrier polyol slurry is consistent with the type of polyol solvent in step 1.
[0014] Furthermore, in step 1, the solute in the dispersing aid solution is at least one of tetraethylammonium hydroxide, ethylenediamine, propylenediamine, ethanolamine, diethanolamine and triethanolamine; the solvent in the dispersing aid solution is at least one of deionized water and polyol; the mass content of the solute in the dispersing aid solution is 5% to 80%. Preferably, in step 1, the solute of the dispersing aid is at least one of tetraethylammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine and triethanolamine; the solvent of the dispersing aid is a combined solvent of deionized water and polyol; the mass content of the solute in the dispersing aid solution is 5% to 50%.
[0015] Preferably, the dispersing aid contains tetraethylammonium hydroxide and / or one or more of other organic amines; more preferably, the mass content of other organic amines in the dispersing aid is 0-20%. Preferably, the polyol is a diol. The dispersing aid is selected from organic bases, which can decompose ammonia. On the one hand, ammonia will react with platinum ions to form platinum ammonia complexes. The small and mobile platinum ions are directly reduced to form platinum particles, which are easy to agglomerate. The ammonia complex of platinum significantly increases the diameter of the metal complex due to the protection of the ligand. This spatial barrier effect constructs many dispersed micro-regions in the reduction reaction, which is conducive to the preparation of ultrafine platinum nanoparticles. On the other hand, the organic base can be used as a pH regulator for the reaction system. In the method of reducing platinum with polyols, in an alkaline environment, it is conducive to the size control of platinum particles.
[0016] Furthermore, in step 1, the platinum precursor and the polyol solvent are mixed evenly, and then the dispersion aid solution is added by atomizing spray, and the addition time is controlled to be 0.5h to 1h, mixed evenly, and a coordination reaction occurs at a temperature of 30°C to 90°C to obtain the first material. Through a large number of experimental investigations by the inventors, it is found that the feeding method and rate of the dispersion aid solution are closely related to the performance of the platinum-carbon catalyst product. Too slow or too fast a feeding rate will cause a significant decrease in the performance of the final product. The feeding rate of the dispersion aid solution will cause differences in the concentration of the dispersion aid in each region, and the ammonia concentration and pH around the platinum ions are different, thereby affecting the rate at which the coordination reaction occurs. If the feeding rate is too slow, the difference in ammonia concentration in each region is too large, resulting in insufficient supply of ammonia ligands required for the platinum coordination reaction. The ammonia coordination numbers of the complexes generated in each region are different, and the spatial resistance of the ligands to the platinum ions is different, resulting in poor uniformity of the platinum particles after reduction and a wide distribution of the particle size of the platinum particles; if the feeding rate is too fast, a large number of complexes are instantly generated in each region of the solution, and the probability of collision and merging increases significantly, which will cause the size of the platinum particles after reduction to be larger. Preferably, in the step 1, the platinum precursor and the polyol solvent are mixed evenly, and then the dispersing aid solution is added by atomizing spraying, and the addition time is controlled to be 0.5h~1h, and mixed evenly to obtain the first material. More preferably, in the step 1, the platinum precursor and the polyol solvent are mixed evenly, and then the dispersing aid is added by atomizing spraying, and the addition time is controlled to be 0.8h~1h, and mixed evenly to obtain the first material.
[0017] Furthermore, the mixing process in step 1 and step 2 is dispersed by at least one of ultrasound, shearing, mechanical and electromagnetic stirring. Preferably, the mixing process in step 1 and step 2 is dispersed by at least two of ultrasound, shearing, mechanical and electromagnetic stirring.
[0018] More preferably, in step 2, the mixing is carried out by a combination of ultrasonic dispersion and high-speed shearing, wherein the ultrasonic dispersion time is 0.3h to 5h, the power is 50W to 500W; the high-speed shearing speed is 4000rpm to 15000rpm, and the shearing time is 0.3h to 5h. Preferably, in step 2, the dispersion of the carbon carrier is carried out by a combination of ultrasonic dispersion and high-speed shearing, wherein the ultrasonic dispersion and high-speed shearing are carried out crosswise, and the operation time of each dispersion method is 0.3h to 1h.
[0019] Further, in step 1, after adding the dispersing aid solution, the pH of the first material is ≥ 9. Preferably, in step 1, after adding the dispersing aid solution, the pH of the first material is ≥ 10. Through a large number of experimental studies by the inventors, it is found that the amount of dispersing aid solution added is closely related to the performance of the platinum-carbon catalyst product. If the pH is too low, the performance of the final product will be significantly reduced.
[0020] Further, in step 3, the second material obtained in step 2 is heated to 130°C to 160°C, kept warm for 2h to 5h, and subjected to reduction reaction; cooled to 50°C to 90°C, deionized water is then added, and stirring is continued for 2h to 5h to obtain a third material. Preferably, in step 3, the second material obtained in step 2 is heated to 140°C to 160°C, reacted for 2h to 4h, and subjected to reduction reaction; cooled to 50°C to 90°C, deionized water is then added, and stirring is continued for 2h to 4h to obtain a third material.
[0021] Furthermore, in step 4, in the platinum-carbon catalyst obtained, the particle size of platinum is 2nm to 5nm. Through a large number of studies by the inventors, it is found that when the particle size of platinum is controlled within a suitable range, the prepared platinum-carbon catalyst has better stability and stronger electrochemical performance. Preferably, in step 4, in the platinum-carbon catalyst obtained, the particle size of platinum is 2.5nm to 5nm. For example, the particle size of platinum is 2.5nm, the particle size of platinum is 3nm, the particle size of platinum is 3.5nm, the particle size of platinum is 4nm, the particle size of platinum is 4.5nm, and the particle size of platinum is 5nm.
[0022] Further, in the step 4, the mass content of platinum in the platinum-carbon catalyst obtained is 20% to 70%. Preferably, in the step 4, the mass content of platinum in the platinum-carbon catalyst obtained is 30% to 70%. For example, the mass content of platinum is 30%, the mass content of platinum is 40%, the mass content of platinum is 50%, the mass content of platinum is 60%, and the mass content of platinum is 70%.
[0023] Another object of the present invention is to provide a product prepared by the above preparation method.
[0024] A platinum-carbon catalyst product prepared by the above-mentioned preparation method of the platinum-carbon catalyst.
[0025] The platinum-carbon catalyst provided by the present invention has platinum nanoparticles uniformly dispersed on a carbon carrier, has weak agglomeration, and has a high electrochemical active area and good stability, thus facilitating wide promotion and application.
[0026] Another object of the present application is to provide a catalyst coating membrane prepared from the above-mentioned platinum-carbon catalyst product.
[0027] A catalyst coating membrane prepared using the above-mentioned platinum-carbon catalyst product.
[0028] In the platinum-carbon catalyst product, platinum nanoparticles are relatively evenly dispersed on the carbon carrier, with weak agglomeration. The platinum-carbon catalyst also has a high electrochemical active area and good stability. The use of this platinum-carbon catalyst product to prepare catalyst coating membranes can be better used in fuel cells and electrode tanks.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] 1. The present invention provides a method for preparing a platinum-carbon catalyst, comprising the following steps: step 1, mixing a platinum precursor and a polyol solvent evenly, then adding a dispersing aid solution, mixing, and performing a coordination reaction at a temperature of 30°C to 90°C to obtain a first material; step 2, adding a carbon carrier polyol slurry to the first material obtained in step 1, mixing, and obtaining a second material; step 3, heating the second material obtained in step 2 to 125°C to 160°C, and keeping the temperature for 1h to 5h; cooling below 90°C; then adding deionized water, and continuing to stir at a constant temperature of 50°C to 90°C for 1h to 5h. Obtain a third material; step 4, concentrating the third material obtained in step 3, and then performing a drying and grinding process to obtain a platinum-carbon catalyst. The method mainly uses carbon carrier, platinum precursor, polyol and dispersing agent as raw materials, controls the addition order, addition amount and addition method of dispersing agent and other factors of raw materials, and prepares platinum carbon catalyst through mixing, reduction, concentration, drying and grinding. The dispersing agent can coordinate with platinum appropriately and can be used as pH regulator of reaction system. The platinum carbon catalyst prepared by the method can adjust the platinum particle size between 2nm and 5nm, and the reduction rate of platinum can reach more than 97%. At the same time, platinum nanoparticles are evenly dispersed on the carbon carrier, with weak agglomeration, and the electrochemical active area of the platinum carbon catalyst is high, the stability is good, and the performance is excellent. After the durability test, the ECSA retention rate can reach 93%. At the same time, the method is simple to operate, does not introduce harmful impurities, does not need to add complex washing and purification processes on the production line, greatly improves production efficiency, and is easy to promote.
[0031] 2. The platinum-carbon catalyst provided by the present invention has platinum nanoparticles uniformly dispersed on a carbon carrier with weak agglomeration, and the platinum-carbon catalyst has a high electrochemical active area, good stability, and excellent performance, which is convenient for wide promotion and application.
[0032] 3. In the platinum-carbon catalyst product, the platinum nanoparticles are relatively evenly dispersed on the carbon carrier, with weak agglomeration. The platinum-carbon catalyst has a high electrochemical active area and good stability. The catalyst coating membrane prepared using this platinum-carbon catalyst product can be better used in fuel cells and electrode tanks. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a transmission electron microscopy (TEM) image of the platinum-carbon catalyst prepared in Example 1 of the present invention.
[0034] Figure 2 This is a transmission electron microscope (TEM) image of the platinum-carbon catalyst prepared in Comparative Example 1 of the present invention.
[0035] Figure 3 This is a transmission electron microscope (TEM) image of the platinum-carbon catalyst prepared in Comparative Example 2 of the present invention.
[0036] Figure 4 Cyclic voltammetry (CV) curves of the platinum-carbon catalysts prepared in Example 1 and Comparative Examples 1-2 of the present invention.
[0037] Figure 5 Linear polarization curves (LSV) of oxygen reduction reactions obtained for the platinum-carbon catalysts prepared in Example 1 and Comparative Examples 1-2 of the present invention.
[0038] Figure 6 CV curves of the platinum-carbon catalysts prepared in Example 1 and Comparative Examples 1-2 of the present invention measured before and after the accelerated aging test experiment.
[0039] Figure 7 This is a graph showing the fuel cell performance test results of the platinum-carbon catalysts prepared in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0040] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] Example 1
[0043] Preparation of platinum-carbon catalyst
[0044] S1. Mixing: Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, a certain mass of 20 wt% tetraethylammonium hydroxide aqueous solution was added within 30 min at a temperature of 40 ° C by atomization spraying until the pH was 10, and stirring was continued for 20 min; a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J was added, and ultrasonic stirring was continued for 20 min.
[0045] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered to 60°C, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0046] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0047] Example 2
[0048] Preparation of platinum-carbon catalyst
[0049] S1. Mixing: Place platinum acetylacetonate (containing 2 g of Pt atoms) in a 2L beaker, add propylene glycol, and shear and disperse for 20 minutes; then add a certain mass of 30 wt% ethylenediamine-propylene glycol solution within 50 minutes at a temperature of 50°C by atomizing and spraying until the pH is 12, and continue stirring for 20 minutes; add a carbon carrier propylene glycol slurry containing 2 g of Ketjenblack EC-300J, and continue ultrasonic shearing for 20 minutes.
[0050] S2, platinum reduction: the material obtained in S1 was heated to 125°C and reacted for 5 hours. After the reduction reaction, the temperature was lowered to 80°C, deionized water was added, and stirring was continued for 5 hours at a stirring rate of 500 rpm.
[0051] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0052] Example 3
[0053] Preparation of platinum-carbon catalyst
[0054] S1. Mixing: Place diaminodinitroplatinum (containing 3g Pt atoms) in a 2L beaker, add butanediol, and stir and disperse for 20min; then add a certain mass of 50wt% triethanolamine-butanediol solution within 60min at a temperature of 60°C by atomizing spray until the pH is 9, and continue stirring for 20min; add a carbon carrier butanediol slurry containing 2g Ketjenblack EC-300J, and continue ultrasonic stirring for 20min.
[0055] S2, platinum reduction: the material obtained in S1 was heated to 160°C and reacted for 1 hour. After the reduction reaction, the temperature was lowered by 70°C, deionized water was added, and stirring was continued for 3 hours at a stirring rate of 400 rpm.
[0056] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0057] Example 4
[0058] Preparation of platinum-carbon catalyst
[0059] S1. Mixing: Place diaminodinitroplatinum (containing 2g Pt atoms) in a 2L beaker, add triethylene glycol solution, and ultrasonically disperse for 20min; then add a certain mass of 30wt% tetraethylammonium hydroxide-triethylene glycol solution at a temperature of 30°C by atomizing spray within 30min until the pH is 11, and continue stirring for 20min; add carbon support triethylene glycol slurry containing 3g Ketjenblack EC-300J, and continue ultrasonic stirring for 20min.
[0060] S2, platinum reduction: the material obtained in S1 was heated to 150°C and reacted for 3 hours. After the reduction reaction, the temperature was lowered by 80°C, deionized water was added, and stirring was continued for 3 hours at a stirring rate of 800 rpm;
[0061] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0062] Example 5
[0063] Preparation of platinum-carbon catalyst
[0064] S1. Mixing: Place platinum acetylacetonate (containing 2 g of Pt atoms) in a 2L beaker, add ethylene glycol solution, and ultrasonically disperse for 20 minutes; then add a certain mass of 40 wt% tetraethylammonium hydroxide-ethylene glycol solution at a temperature of 30°C by atomizing spray within 30 minutes until the pH is 10, and continue stirring for 20 minutes; add carbon support ethylene glycol slurry containing 2 g of Ketjenblack EC-300J, and continue shear stirring for 20 minutes.
[0065] S2, platinum reduction: the material obtained in S1 was heated to 145°C and reacted for 2.5 hours. After the reduction reaction, the temperature was lowered by 60°C, deionized water was added, and stirring was continued for 2.5 hours at a stirring rate of 500 rpm;
[0066] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0067] Comparative Example 1
[0068] Compared with Example 1, no dispersing aid was added during the preparation of the platinum-carbon catalyst in Comparative Example 1, and other operating steps and conditions were the same, as follows:
[0069] Preparation of platinum-carbon catalyst
[0070] S1. Mixing: Place platinum nitrate (containing 2 g of Pt atoms) in a 2 L beaker, add ethylene glycol, and ultrasonically disperse for 20 min; add carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J, and continue ultrasonic stirring for 20 min.
[0071] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0072] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0073] Comparative Example 2
[0074] The difference between Comparative Example 2 and Example 1 is that the organic alkaline solution is replaced with other alkaline solutions, and the specific operation is as follows:
[0075] Preparation of platinum-carbon catalyst
[0076] S1. Mixing: Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, a certain mass of 20 wt% potassium hydroxide solution was added within 30 min at a temperature of 40 ° C by atomization spraying until the pH was 10, and stirring was continued for 20 min; a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J was added, and ultrasonic stirring was continued for 20 min.
[0077] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0078] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0079] Comparative Example 3
[0080] Compared with Example 1, Comparative Example 3 uses other platinum precursors.
[0081] Preparation of platinum-carbon catalyst
[0082] S1. Mixing: Place chloroplatinic acid (containing 2 g of Pt atoms) in a 2L beaker, add ethylene glycol, and ultrasonically disperse for 20 min; then add a certain mass of 20 wt% tetraethylammonium hydroxide aqueous solution by atomizing spray within 30 min at a temperature of 40°C until the pH is 10, and continue stirring for 20 min; add a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J, and continue ultrasonic stirring for 20 min.
[0083] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0084] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0085] Comparative Example 4
[0086] Compared with Example 1, Comparative Example 4 adopts a slow dropwise addition method to add the dispersing aid solution.
[0087] Preparation of platinum-carbon catalyst
[0088] S1. Mixing: Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, at a temperature of 40 ° C, a certain mass of 20 wt% tetraethylammonium hydroxide aqueous solution was added dropwise at a rate of 0.5 mL / min using a single-point feeding method, and the amount added was the same as that in Example 1, and stirring was continued for 20 min; a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J was added, and ultrasonic stirring was continued for 20 min.
[0089] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0090] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0091] Comparative Example 5
[0092] Compared with Example 1, in Comparative Example 5, the dispersing aid solution was added in a rapid feeding manner.
[0093] Preparation of platinum-carbon catalyst
[0094] S1. Mixing: Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, at a temperature of 40° C., a certain mass of 20 wt % tetraethylammonium hydroxide aqueous solution was added within 10 min by a single-point addition method, and the addition amount was the same as that in Example 1, and stirring was continued for 20 min; a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J was added, and ultrasonic stirring was continued for 20 min.
[0095] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0096] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0097] Comparative Example 6
[0098] Compared with Example 1, Comparative Example 6 changes the order of adding raw materials.
[0099] Preparation of platinum-carbon catalyst
[0100] S1. Mixing: 2 g of Ketjenblack EC-300J was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic stirring was performed for 20 min; then, at a temperature of 40° C., a certain mass of 20 wt % tetraethylammonium hydroxide aqueous solution was added by atomization spraying within 30 min, and the added amount was the same as that in Example 1, and stirring was continued for 20 min; then, platinum nitrate ethylene glycol solution (containing 2 g of Pt atoms) was added, and ultrasonic dispersion was applied for 20 min.
[0101] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0102] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0103] Comparative Example 7
[0104] Compared with Example 1, Comparative Example 7 changes the time point of adding the carbon carrier.
[0105] Preparation of platinum-carbon catalyst
[0106] S1. Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2 L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, a certain mass of 20 wt% tetraethylammonium hydroxide aqueous solution was added within 30 min at a temperature of 40° C. by atomization spraying, and the added amount was the same as that in Example 1, and stirring was continued for 20 min;
[0107] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction was completed, a carbon carrier ethylene glycol slurry containing 2 g Ketjenblack EC-300J was added and ultrasonic stirring was continued for 20 minutes. The temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm.
[0108] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0109] Comparative Example 8
[0110] In Comparative Example 8, compared with Example 1, the amount of the dispersing aid solution added was adjusted and the pH was controlled.
[0111] Preparation of platinum-carbon catalyst
[0112] S. Platinum nitrate (containing 2 g of Pt atoms) was placed in a 2L beaker, ethylene glycol was added, and ultrasonic dispersion was performed for 20 min; then, a certain mass of 20 wt% tetraethylammonium hydroxide aqueous solution was added within 30 min at a temperature of 40°C by atomization spraying until the pH was 7, and stirring was continued for 20 min; a carbon carrier ethylene glycol slurry containing 2 g of Ketjenblack EC-300J was added, and ultrasonic stirring was continued for 20 min.
[0113] S2, platinum reduction: the material obtained in S1 was heated to 140°C and reacted for 2 hours. After the reduction reaction, the temperature was lowered, deionized water was added, and stirring was continued for 2 hours at a stirring rate of 600 rpm;
[0114] S3, concentration and drying: Filter by suction, transfer the obtained filter cake into a vacuum drying oven, and dry it at 80°C for 12 hours; after cooling to room temperature, take it out and grind it to obtain platinum-carbon catalyst powder.
[0115] Test 1:
[0116] The mass content of platinum in the platinum-carbon catalysts prepared in Examples 1-5 and Comparative Examples 1-8 was tested by thermogravimetry. The test results are shown in Table 1.
[0117] The material structure of the platinum-carbon catalysts prepared in Examples 1-5 and Comparative Examples 1-8 was determined by X-ray diffraction, and the average particle size of platinum was calculated according to the Scherrer formula. The test results are shown in Table 1.
[0118] Electrochemical performance test:
[0119] Preparation of working electrode: Weigh 7.6 mg of the platinum-carbon catalyst obtained in Examples 1-5 and Comparative Examples 1-8 above, respectively, and transfer to a 20 ml glass sample bottle. Then add 7.6 mL of ultrapure water and 2.4 mL of isopropanol, ultrasonically disperse for 30 min, then cool to room temperature, drop 40 μL of 5 wt% Nafion solution, and continue ultrasonication for 10 min to obtain catalyst ink. Apply the ink dropwise on a clean glassy carbon electrode, and after drying, obtain a working electrode. The amount of platinum on the working electrode is: 10 μg / cm 2 In the electrochemical test, a saturated calomel electrode is used as the reference electrode, a graphite electrode is used as the counter electrode, and a three-electrode test system is built.
[0120] Cyclic voltammetry test: Electrochemical activation and cyclic voltammetry (CV) were performed in a nitrogen-saturated 0.1 M HClO4 electrolyte. The scanning potential range was 0.05-1.2 V vs. RHE (the potential values in the present invention, unless otherwise specified, refer to the relative reversible hydrogen electrode potential), the scanning rate was 50 mV / s, the standard CV curve was measured, and the electrochemically active area (ECSA) was calculated. The results are shown in Table 1.
[0121] Oxygen reduction activity test: Electrochemical linear polarization curve test (LSV) was performed in an oxygen-saturated 0.1M HClO4 electrolyte. The scanning potential range was 0.05-1.03V vs. RHE, and the scanning rate was 10mV / s. The standard LSV curve was measured and the mass activity (MA) was calculated. The results are shown in Table 1.
[0122] Durability test: Perform electrochemical accelerated aging test in 0.1M HClO4 electrolyte, scan potential range 0.6~0.95V vs.RHE, scan rate 100mV / s, perform 30000 cycles of CV cycle test. Compare the ECSA changes before and after the durability test.
[0123] Table 1
[0124]
[0125]
[0126] In Example 1-5, the platinum particle size can be regulated to 2-5 nm by adjusting the pH to ≥ 9 by a dispersing aid. As the pH increases, the platinum particle size gradually decreases, and the platinum mass content of the obtained platinum-carbon catalyst is very close to the platinum feed ratio, and the platinum reduction rate is ≥ 97%. At the same time, the platinum nanoparticles are evenly dispersed on the carbon carrier, with weak agglomeration, and the platinum-carbon catalyst has a high electrochemical active area, good stability, and excellent performance. After the durability test, the ECSA retention rate can reach 93%.
[0127] The difference between Comparative Example 1 and Example 1 is that no dispersing agent is used, the platinum particle size is too large, the platinum utilization rate is low, and the measured electrochemical performance is reduced. Comparative Examples 2-3 are synthesized using materials containing chloride ions or alkali metal cations, and are not washed and impurity-removed. Although the average particle size of platinum is small, the electrochemical performance of the prepared platinum-carbon catalyst is significantly reduced due to the residual harmful impurities, especially chloride ions will be adsorbed on the active sites of platinum, blocking the adsorption of oxygen and the reduction of oxygen. Comparative Examples 4-5 adopt a single-point feeding method and slow down or speed up the addition rate of the dispersing agent respectively. The average particle size of platinum is too large, indicating that the addition method and rate control of the dispersing agent solution play an important role in the mixing stage before platinum reduction. The addition rate of the dispersing agent solution affects the generation rate of the ammonia complex of platinum, thereby being able to regulate the platinum particle size. Comparative Example 6 adjusts the order of addition of the raw materials. When the dispersing agent first contacts the carbon carrier, the ammonia or ammonium ions decomposed by the dispersing agent will react with the surface groups of the carrier, occupying the effective sites in advance, resulting in agglomeration during platinum loading, and the platinum particle size is too large. In Comparative Example 7, the dispersing aid is first mixed with the platinum precursor and then reduced at a high temperature, and then the carbon carrier slurry is added. The electrochemical active area of the obtained platinum-carbon catalyst is relatively low. In the embodiment, the carbon carrier is added to the reaction system before the platinum reduction. Since the carbon carrier is porous and has a high specific surface area, the ammonia complex of platinum can be pre-adsorbed on the surface or pores of the carbon carrier. The rough surface characteristics of the carbon carrier can play a certain limiting role, promoting the platinum particles generated by reduction to be more evenly dispersed on the carrier surface.
[0128] Therefore, by adjusting the order and amount of raw material addition and the method of adding the dispersing aid solution, a platinum-carbon catalyst with a smaller platinum particle size and higher uniformity can be obtained, and the platinum-carbon catalyst has a high electrochemical active area and good stability.
[0129] Test 2
[0130] Morphology test: Transmission electron microscopy (TEM) was used to characterize the loading and agglomeration of the active component platinum particles of the platinum-carbon catalysts obtained in the examples and comparative examples. Figure 1-3 shown.
[0131] Fuel cell performance testing
[0132] Preparation of membrane electrode: The catalysts prepared in Example 1 and Comparative Examples 1-2 were sprayed on both sides of the polymer electrolyte membrane to prepare catalyst coated membrane (CCM), and assembled with carbon paper into membrane electrode assembly (MEA) for testing, and IV curves were obtained (see Appendix for details). Figure 7 ). The amount of platinum used (anode / cathode): 0.1 mg cm -2 / 0.3mg·cm -2 .
[0133] Test conditions: battery operating temperature: 75°C; relative humidity (anode / cathode): 100% / 100%; reaction gas stoichiometric ratio (anode / cathode): hydrogen 1.5 / air 2.5; back pressure (anode / cathode): 0.1MPa / 0.1MPa. The horizontal axis in the figure is the current density (unit: A / cm 2 ), the vertical axis is voltage (unit: V).
[0134] Result analysis:
[0135] (1) By Figure 1 and Figure 2 As shown in the transmission electron microscope images of Example 1 and Comparative Example 1, it can be seen that the dispersing agent helps to regulate the platinum particle size of the platinum carbon catalyst. The difference between Comparative Example 1 and Example 1 is that no dispersing agent is used. Figure 2 Platinum particles can be seen agglomerated in many areas, and the sizes of platinum particles are uneven. Figure 1 There is almost no agglomeration problem in the process. Combined with the platinum particle size results obtained by XRD, it shows that the dispersing aid plays a key role in the platinum reduction stage, which can effectively improve the platinum nucleation and growth mechanism and obtain platinum fine nanoparticles with narrow particle size distribution and high uniformity.
[0136] (2) By Figure 1 and Figure 3 As shown in the transmission electron microscope images of Example 1 and Comparative Example 2, it can be seen that the dispersing aid helps to improve the platinum dispersion of the platinum carbon catalyst. The difference between Comparative Example 2 and Example 1 is that potassium hydroxide solution is used to control the pH of the reaction solution. Figure 3 The platinum particles are small in size, but the platinum particles are agglomerated and have poor distribution uniformity and uneven density on the carbon carrier. Figure 1 The size of the platinum particles is small and the dispersion is high. In Example 1, a dispersing agent is added. On the one hand, the dispersing agent can decompose ammonia, which reacts with platinum ions to form ammonia complexes of platinum. The ammonia ligands greatly increase the barrier between metal ions, so that many dispersed micro-regions are constructed in the reduction reaction, thereby obtaining ultrafine platinum nano-colloids in the high-temperature reduction reaction. On the other hand, the dispersing agent can be used as a pH regulator. In an alkaline system, the surface of the platinum colloid obtained after reduction is adsorbed by hydroxide (OH - ) carries a negative charge, which is beneficial to the balance and stability of platinum colloid and inhibits the agglomeration of platinum after reduction, which further provides a guarantee for the preparation of nano-dispersed platinum-carbon catalysts.
[0137] (3) By Figure 4-5 As shown, by comparing the CV and LSV curves of Example 1 and Comparative Examples 1-2, the electrochemical active area ECSA and mass activity MA of Example 1 are significantly higher than those of Comparative Examples 1-2, indicating that the dispersing aid can effectively improve the utilization rate of platinum by improving the platinum particle size and platinum dispersion, and enhance the oxygen reduction reaction performance of the platinum-carbon catalyst.
[0138] (4) Based on Figure 6 As shown in Table 1, the durability tests of Example 1 and Comparative Examples 1-2 are compared. After the accelerated aging experiment, the electrochemical active area retention rate of Example 1 is the highest, indicating that the accelerated aging test has the smallest effect on the platinum particle size and platinum dispersion of the platinum-carbon catalyst prepared in Example 1, while the CV curve of Comparative Examples 1-2 has a large change range. The reason for the sharp drop in ECSA may be that the originally unevenly dispersed platinum particles are more likely to migrate and agglomerate, and there may even be platinum particles falling off. The initial activity and durability of Example 1 are higher than those of Comparative Examples 1-2, mainly because the dispersing aid improves the platinum particle size and platinum dispersion, and the dispersing aid also interacts with the surface groups of the carbon carrier to enhance the anchoring effect of the active component platinum and the carrier, improves the stability of the platinum particles, inhibits the migration, agglomeration and growth of the platinum particles, and enhances the durability of the platinum-carbon catalyst.
[0139] (5) Based on Figure 7 Comparing the fuel cell tests of Example 1 and Comparative Examples 1-2, the single cell performance of Example 1 is significantly higher than that of Comparative Examples 1-2, indicating that adding a dispersing aid during the preparation of the platinum-carbon catalyst helps to improve the platinum particle size and platinum dispersion, and the effective utilization rate of the precious metal platinum is increased, thereby improving the membrane electrode performance.
[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a platinum-carbon catalyst, characterized in that: The following steps are involved: Step 1, mixing the platinum precursor and the polyol solvent evenly, then adding the dispersing aid solution by atomizing spray, and controlling the adding time to be 0.5h to 1h, mixing evenly, and performing coordination reaction at a temperature of 30°C to 90°C to obtain a first material; the platinum precursor is at least one of platinum nitrate, platinum acetylacetonate, hexahydroxyplatinic acid and diaminodinitroplatinum; the solute in the dispersing aid solution is at least one of tetraethylammonium hydroxide, ethylenediamine, propylenediamine, ethanolamine, diethanolamine and triethanolamine; after adding the dispersing aid solution, the pH of the first material is ≥9; Step 2, adding the carbon support polyol slurry to the first material obtained in step 1, mixing evenly, to obtain a second material; Step 3, heating the second material obtained in step 2 to 125°C to 160°C and keeping it warm for 1h to 5h; cooling it to below 90°C; then adding deionized water, and continuing to stir at a constant temperature of 50°C to 90°C for 1h to 5h to obtain a third material; Step 4: After concentrating the third material obtained in step 3, dry and grind it to obtain a platinum-carbon catalyst.
2. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: In the step 1, the platinum precursor is at least one of platinum nitrate, platinum acetylacetonate, hexahydroxyplatinic acid and diaminodinitroplatinum; the polyol solvent is at least one of ethylene glycol, propylene glycol, glycerol, butylene glycol, diethylene glycol, triethylene glycol and tetraethylene glycol; in the step 2, in the carbon carrier polyol slurry, the carbon carrier is at least one of carbon black, activated carbon, graphite carbon, carbon nanotubes, graphene and mesoporous carbon; in the carbon carrier polyol slurry, the polyol is at least one of ethylene glycol, propylene glycol, glycerol, butylene glycol, diethylene glycol, triethylene glycol and tetraethylene glycol.
3. The method for preparing a platinum-carbon catalyst according to claim 2, characterized in that: In step 1, the solute in the dispersing aid solution is at least one of tetraethylammonium hydroxide, ethylenediamine, propylenediamine, ethanolamine, diethanolamine and triethanolamine; the solvent in the dispersing aid solution is at least one of deionized water and a polyol; and the mass content of the solute in the dispersing aid solution is 5% to 80%.
4. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: In the step 1, the platinum precursor and the polyol solvent are mixed evenly, and then the dispersion aid solution is added by atomization spraying, and the adding time is controlled to be 0.5h to 1h, and the mixture is mixed evenly to obtain the first material.
5. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: The mixing process in step 1 and step 2 is performed by dispersing using at least one of ultrasonic, shearing, mechanical and electromagnetic stirring.
6. The method for preparing a platinum-carbon catalyst according to claim 1, characterized in that: In the step 1, after adding the dispersing aid solution, the pH of the solution is ≥9.
7. The method for preparing a platinum-carbon catalyst according to claim 6, characterized in that: In the step 4, the particle size of platinum in the obtained platinum-carbon catalyst is 2nm to 5nm.
8. The method for preparing a platinum-carbon catalyst according to claim 7, characterized in that: In step 4, the mass content of platinum in the obtained platinum-carbon catalyst is 20% to 70%.
9. A platinum-carbon catalyst product prepared by the preparation method of the platinum-carbon catalyst as described in any one of claims 1 to 8.
10. A catalyst coating membrane prepared using the platinum-carbon catalyst product as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of multi-walled carbon nanotube loaded high-density high-dispersion nano platinum counter electrode
CN102903537B
Catalyst with high metal loading capacity as well as preparation and application thereof
CN112823880A
High-loading-capacity high-dispersion platinum-carbon catalyst and preparation method of amino ligand of high-loading-capacity high-dispersion platinum-carbon catalyst
CN114914463A